Effects of occupational therapy synchronized with dual transcranial direct current stimulation on upper limb function and electroencephalography power in subacute stroke patients: A randomized, double-blind, controlled study - Ling Gao; Fengming Chu; Xuan Liu; Jie Chen; Ming Zhang; Yuming Zhang (PLoS ONE, 2025)
Background Occupational therapy (OT) and transcranial direct current stimulation (tDCS) are both important methods for promoting the recovery after stroke. There are limited researches that simultaneously apply both methods and investigate their effects on upper limb function. Objective To investigate the effects of OT synchronized with dual tDCS on upper limb motor function and Electroencephalogram (EEG) power in subacute stroke patients. Methods Forty-five subacute stroke patients were randomly assigned to control group (n = 23) and experimental group (n = 22), receiving sham and real dual tDCS concurrent with OT respectively, five times a week, for a duration of two weeks. Upper limb motor function and cortical EEG power were evaluated by Fugl-Meyer Assessment Upper Extremity (FMA-UE), Modified Barthel Index (MBI) and Action Research Arm Test (ARAT), Delta/Alpha Ratio (DAR) and pairwise derived Brain Symmetry Index (pdBSI) at baseline and two weeks. Results Finally, a total of 39 patients completed the study and were included in the analysis. The results revealed that participants in the experimental group showed a significant better evolution for FMA-UE (p < 0.001), MBI (p = 0.034), DAR in the primary motor cortex (M1) area (p = 0.022) and pdBSI (p = 0.025) compared to the control group. Conclusions In subacute stroke patients, the central-peripheral combined stimulation approach, which involves dual tDCS (central stimulation) and synchronous OT (peripheral sensory-motor stimulation) enhanced the effects of OT alone, leading to greater improvements in upper limb function and normalization of brain activity. Trial registration This trial was registered in the Chinese Clinical Trial Registry (No. ChiCTR2400082749).